Therapeutic perspectives of exosomes in glucocorticoid-induced osteoarthrosis - Lv, Bin; Cheng, Zhangrong; Yu, Yajie; Chen, Yuhang; Gan, Weikang; Li, Shuai; Zhao, Kangcheng; Yang, Cao; Zhang, Yukun (Frontiers in Surgery, 2022)
Exosomes are widely involved in a variety of physiological and pathological processes. These important roles are also hidden in the physiological processes related to bone. Chondrocytes, osteoblasts, synovial fibroblasts, and bone marrow mesenchymal stem cells produce and secrete exosomes, thereby affecting the biology process of target cells. Furthermore, in the primary pathogenesis of osteoarthrosis induced by steroid hormones, mainly involve glucocorticoid (GC), the exosomes have also widely participated. Therefore, exosomes may also play an important role in glucocorticoid-induced osteoarthrosis and serve as a promising treatment for early intervention of osteoarthrosis in addition to playing a regulatory role in malignant tumors. This review summarizes the previous results on this direction, systematically combs the role and therapeutic potential of exosomes in GC-induced osteoarthrosis, discusses the potential role of exosomes in the treatment and prevention of GC-induced osteoarthrosis, and reveals the current challenges we confronted.